Analisis faktor yang mempengaruhi perilaku seksual pada remaja SMA kota Lhokseumawe - Lubis, Putri Sabrina; Khairunnisa , Cut; Wahyuni , Hendra (Journal of Pharmaceutical and Sciences, 2025)
Adolescent sexual behavior is an important issue in health education. This can be influenced by knowledge, attitudes, the role of parents, peers, information media, religion, and the role of teachers and schools. This study aims to analyze the factors that affect the sexual behavior of adolescents of Lhokseumawe City State High School. This research method uses a descriptive analytical research design with a cross-sectional approach. The sample in this study was 342 students of Lhokseumawe City State High School. Sampling used stratified random sampling technique and data collection was carried out using a questionnaire. The results of the study showed that most teenagers were in the age range of 17-19 years and most were female, the sexual behavior of high school teenagers in Lhokseumawe City showed that most were not involved in deviant sexual behavior. Factors that influence the sexual behavior of high school teenagers in Lhokseumawe City show that adolescent knowledge is generally good. Most show positive attitudes, have good parental roles, are significantly influenced by peers, and only a few access information media related to pornography. The data obtained were analyzed using the Chi-square test. This proves that there is a significant relationship between knowledge, attitude, parental role, peer role, and information media with adolescent sexual behavior in Lhokseumawe City State High School. with the results of the study showing p < (0.05). Thus, the research is expected to contribute positively to understanding and addressing deviant sexual behavior among adolescents and to support the development of better protection policies for adolescents in Lhokseumawe.